Liver function disorders in COVID-19 patients admitted to Tishreen University Hospital in Lattakia - الليوا, يزن; اسماعيل حمَاد ,; يوسف زريق, (Latakia University Journal -Medical Sciences Series, 2023)
Purpose : We aim to study the effect of liver function disorders (Alanine aminotransferase ALT / Aspartate aminotransferase AST / Total Bilirubin T.Bili / Direct (Conjugated) Bilirubin D.Bili) on prognosis in COVID-19 patients , with evaluation of a statistically significant relationship between infection with COVID-19 and liver function disorders in terms of gender , age , average hospitalization period , need for mechanical ventilation (ventilator / intensive care unit ICU) and mortality. Methods :A retrospective cohort study was performed that included 471 COVID-19 patients admitted to the isolation department at Tishreen University Hospital in Lattakia in the period between 2020 – 2021 . We did a retrospective study of the files of patients who met the admission criteria , and studied the aforementioned variables and liver function disorders (ALT / AST / AST/ALT Ratio / T.Bili / D.Bili). Results :Our study included 471 COVID-19 patients , their average age was 63.21 years , and the percentage of males was (61.36%) (Sex Ratio M;F 1.59:1). The patients were divided according to liver function tests conducted upon admission into two groups , the group of patients who had normal liver function tests (n = 190 , 40.34%) and the group of patients who had abnormal liver function tests (n = 281 , 59,66%). When comparing the results between the two study groups , we found no statistically significant difference in terms of age (P-value = 0.176) , sex (P-value = 0.165515) , and the average hospitalization period (P-value = 0.063425) , between the two study arms. The total death rate reached 251 deaths ( 53.29%) , and this rate was higher in the group of patients with impaired liver functions (60.49%) compared to (42.63%) in the group of patients with normal liver functions , and this constituted a statistically significant difference (P-value = 0.000092) . Also the rate of need for mechanical ventilation (ventilator / intensive care unit) was higher in the group of patients with abnormal liver functions (33.45%) compared to (13.16%) in the group of patients with normal liver functions , with a statistically significant difference (P-value = 0.000057). Conclusion : Our study showed that hepatic injury in COVID-19 had a significant effect on survival , the need for mechanical ventilation (ventilator / intensive care unit) compared to the absence of this injury , but it did not significantly affect the average hospitalization period in patients with COVID-19. We need more studies and research to characterize causes and the extent of liver damage in COVID-19 , in addition to the effect of SARS-CoV-2 infection on chronic liver diseases.